Instrumen Musik Ekstrakurikular Pianika di SDN 2 Puja Mulia, Kabupaten Bener Meriah - Aida Fitri; Sakdiyah Sakdiyah; Taat Kurnita (Universitas Syiah Kuala, 2022)
Extracurricular is an activity that is carried out outside the hours of learning. Extracurricular aims to hone the talents and interests of students in various fields of science. This study aims to describe the extracurricular activities of musical instruments pianika and any constraints found teachers in extracurricular activities of musical instruments pianika in SDN 2 Puja Mulia Bandar District Bener Meriah Regency. This research approach is qualitative with descriptive type. Data collection techniques with observation, interviews, and documentation. Data analysis with data reduction, data presentation, data verification. This research was conducted in SDN 2 Puja Mulia Bandar District Bener Meriah Regency. Based on research data that the learning process in the extracurricular activities of musical instruments pianika in SDN 2 Puja Mulia Bandar District Bener Meriah Regency conducted in three meetings. At each meeting consists of three stages of the process learning is the initial stage, the core stage and the closing stage. At the first meeting the teacher gives only insight and basic knowledge of music. At the second meeting, the teacher taught about the technique of searching and blowing and gave the material of the song entitled “Cicak-Cicak on The Wall”. At the third meeting, the teacher repeated the song that had been taught and conducted a practical test. This test is done only to see the skills of students in playing a musical instrument pianika. The constraints on extracurricular activities musical instruments pianika there are three constraint factors consisting of factors: (1) Facilities and infrastructure factors, (2)Family Factor, and (3) Student Factor.